INTERACTION BETWEEN A TECHNICAL UNIVERSITY AND THE DEPARTMENTS UNDER ENTERPRISES - Sergey M. Dmitriev; Tatiana I. Ermakova; Evgeny G. Ivashkin (Высшее образование в России)
The article describes the experience of Nizhny Novgorod State Technical University n.a. R.E.Alekseev in creation of the departments attached to high-tech enterprises. Such departments help to prepare qualified engineering personnel for enterprises. While studying at the departments, students can easy accommodate themselves to the specificity and working conditions and get ready for practice-oriented activities at enterprise.